2019
DOI: 10.1017/s0022029919000840
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the smallholder dairy value chain: a system dynamics ex-ante impact assessment in Tanzania's Kilosa district

Abstract: This paper examines ex-ante impacts of two policy interventions that improve productivity of local-breed cows through artificial insemination (AI) and producers’ access to distant markets through a dairy market hub. The majority of cattle in Kilosa district in Tanzania are local low productivity breeds kept by smallholders and agro-pastoralists. Milk production is seasonal, which constrains producers’ access to distant urban markets, constrains producers’ incomes and restricts profitability in dairy processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Research about the important drivers or indicators or factors and the measurement tool for assessing the performance of the dairy supply chain can be found in Prakash and Pant (2013), Kumar (2014), Kumar and Mohan (2014), Okano et al (2014), Mor et al (2017, 2018), Susanty et al (2018), Susanty et al (2019), Dizyee et al (2019) and Bórawski et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research about the important drivers or indicators or factors and the measurement tool for assessing the performance of the dairy supply chain can be found in Prakash and Pant (2013), Kumar (2014), Kumar and Mohan (2014), Okano et al (2014), Mor et al (2017, 2018), Susanty et al (2018), Susanty et al (2019), Dizyee et al (2019) and Bórawski et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, using ISM methodology, Mor et al (2018) identified PIs that make the most contribution to the Indian dairy industry sector, namely, the information-technology-enabled support system, brand management and featured products, responsiveness in shipment accuracy and milk wastage management. Susanty et al (2019) and Dizyee et al (2019) used system dynamic methodology to simulate the causal relationship between several factors that contributed to the performance of the dairy supply chain in Indonesia and Kilosa, a district in Tanzania, respectively. In this case, Susanty et al (2019) proposed five policy scenarios, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to FAO (2011a), "one of the major constraints for intensification of small-scale livestock production is the lack of good quality feed resources." Dairy animals in low-income countries often suffer from malnutrition in several months throughout the year as a result of climatic, economic, and management conditions (Val-Arreola et al, 2004;Dizyee et al, 2019). Animal health and milk production cannot be sustained if dairy cows are underfed and undernourished.…”
Section: Animal Nutritionmentioning
confidence: 99%
“…However, gender awareness and integration in local government activities at the village level was still low, though partially mitigated by gender awareness training and deliberate inclusion as group leaders by MZ. These inadequacies require additional public investments for a longer period before private capital can yield positive returns (Dizyee, Baker, and Omore 2017;Kilelu et al 2017).…”
Section: Assessing Changes and Assumptionsmentioning
confidence: 99%